Utilization of Liquid Smoke to Suppress Blood Diseases on Bananas and Its Effects on the Plant Growth - Imas Aisyah; Meity Suradji Sinaga; Abdjad Asih Nawangsih; Giyanto Giyanto; Gustan Pari (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Liquid smoke is reported to be effective to inhibit some bacteria. The study aimed to evaluate the effects of liquid smoke (LS) from coconut shell (CS-LS), pinecone (P-LS), and oil palm branch (OPB-LS) on the incidences of blood disease, induced resistance to Ralstonia syzygii subsp. celebesensis, and plant growth. Two days after banana seedlings were treated with LS, ethylene, auxin, lignin, activities of the enzymes of peroxidase (POD) and phenylalanine ammonia lyase (PAL) on the root of the banana seedlings were measured. Then, the seedlings were inoculated by R. syzygii subsp. celebesensis. The plant growth and incidence of blood diseases were observed daily and the 31st day after the application of LS and this bacteria inoculation. The results showed that the CS-LS, P-LS, and OPB-LS at all tested concentration could suppress the incidence of blood diseases up to 100 %, induce resistance of banana seedlings to the R. syzygii subsp. celebesensis with increased levels of ethylene, auxin, lignin, activities of POD and PAL, and plant growth, significantly. Based on the effectiveness of this bacterial control and the ability to promote the growth of banana seedlings test, it is recommended that the most effective treatment is P-LS 0.5 %.